2009
DOI: 10.1007/s10549-009-0346-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in hormone replacement therapy use and declining breast cancer incidence in the Belgian province of Limburg

Abstract: Breast cancer is the most common female cancer in Europe, but its incidence and mortality are rapidly changing across Europe. The early termination of the women's health initiative (WHI) trial, after the detection of an increased breast cancer risk in hormone replacement therapy (HRT) users, was followed by strong declines of HRT use worldwide. We investigated whether the reduction of HRT sales affected breast cancer incidence in the Belgian province Limburg. All women registered in the Limburg Cancer Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
1
15
1
1
Order By: Relevance
“…Lobular cancers have also been postulated to be particularly sensitive to hormonal stimulation. While a few investigators have reported larger recent decreases in incidence for lobular cancers than for ductal cancers [14,20], we found no evidence of a different incidence pattern for the small subgroup of lobular carcinomas available for analyses in the present study.…”
Section: Ddd/1000contrasting
confidence: 93%
See 1 more Smart Citation
“…Lobular cancers have also been postulated to be particularly sensitive to hormonal stimulation. While a few investigators have reported larger recent decreases in incidence for lobular cancers than for ductal cancers [14,20], we found no evidence of a different incidence pattern for the small subgroup of lobular carcinomas available for analyses in the present study.…”
Section: Ddd/1000contrasting
confidence: 93%
“…In an analysis based on data from nine US cancer registries, Ravdin et al reported a 7% overall decrease in incidence between 2002 and 2003 in women older than 50 years of age and particularly for estrogen receptor positive tumors [1]. Subsequent studies from the US, Canada, Australia, France, Switzerland, Germany, Great Britain, Belgium, and the Nordic countries have also reported reductions in breast cancer incidence [2][3][4][5][6][7][8][9][10][11][12][13][14]. These changes have been hypothesized to be a result of a dramatic decline in the use of hormone replacement therapy (HRT) following the 2002 release of the report from the Women's Health Initiative (WHI) hormone trial [15].…”
Section: Introductionmentioning
confidence: 99%
“…The association with HRT use is stronger for lobular carcinoma than for ductal carcinoma [17,18]. In Belgium, Vankrunkelsven et al [7] found a larger decline in invasive lobular than in ductal carcinomas, while inverse results were found in the USA [19]. For Geneva, we previously reported a disproportionate increase in lobular cancer incidence during the period 1976-1999.…”
Section: Discussionmentioning
confidence: 66%
“…After that the Women's Health Initiative (WHI) randomized controlled trial in 2002 reported an increased breast cancer risk among women using hormone replacement therapy (HRT) [1,2], HRT use and breast cancer incidence among post-menopausal women showed an important decline in several countries, including USA, Belgium, France, Australia, United Kingdom, and Germany [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Sie führen diese Reduktion auf den Rückgang der HRT zurück [26]. Dieser Kausalzusammenhang kann zum einen durch Daten aus Deutschland [20,21], zum anderen aber auch mit Daten aus Frankreich [1], Belgien [30] und Australien [6] postuliert werden. Daher ist von einer zunehmenden Zahl langfristig überleben-der Mammakarzinompatientinnen auszugehen.…”
unclassified